Smartphone Applications and Religious Reading among Swaminarayan Hindus. Issue 1 (2nd November 2021) - Mamtora, Bhakti
Abstract : This paper examines how two prominent digital sacred texts, Vachanamrut Study App and Swamini Vato Study App, shape reading and meaning-making practices among members of the Swaminarayan Sampraday in the United States. By analyzing the design and use of applications, I argue that smartphone applications are pedagogical tools that integrate offline modes of textual study and simplify access to the meanings of the teachings. The historical, contextual, and paratextual features of smartphone applications reinforce that the study of sacred texts is an intentional, conscientious, dialogical, and gradual process—a process that enables individuals to fulfill their religious aspirations.